2022
DOI: 10.12688/f1000research.125112.1
|View full text |Cite
|
Sign up to set email alerts
|

Predictive factor of renal function recoverability in upper-tract obstructive uropathy after percutaneous nephrostomy and Double -J stent insertion in Indonesian National Referral Hospital

Abstract: Introduction: Obstructive uropathy (OU) is defined as an alteration in any level of the urinary tract that is caused by abnormalities of its system organs, or external pathological factors. Hydronephrosis and progressive renal impairment are signs of upper-tract OU. OU  accounted to be around 0,9% - 3,8% of prevalence for etiology of hydronephrosis. The aim of OU treatment is to achieve optimal urinary diversion, either by retrograde intra-ureteral stenting or percutaneous drainage. However, improvement of ren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 16 publications
(34 reference statements)
1
0
0
Order By: Relevance
“…This study shows no significant difference between kidney function in nephrostomy and DJ stent postoperatively. Some study shows the same result [2,3]. Meanwhile, Shoshany et al (2015) found that renal function improvement was better after Double-J stent than percutaneous nephrostomy In their study, eGFR after DJ Stent insertion and nephrostomy is 85.5 (69.3-90.6) MDRD, mL/min/1.73 m2 vs. 69 (58.1-80.4) MDRD, mL/min/1.73 m2, a p-value of 0.001 This difference is because patients who undergo nephrostomy have a lower baseline eGFR before the procedure, and renal function tests are carried out over more extended periods [4].…”
Section: Discussionsupporting
confidence: 55%
“…This study shows no significant difference between kidney function in nephrostomy and DJ stent postoperatively. Some study shows the same result [2,3]. Meanwhile, Shoshany et al (2015) found that renal function improvement was better after Double-J stent than percutaneous nephrostomy In their study, eGFR after DJ Stent insertion and nephrostomy is 85.5 (69.3-90.6) MDRD, mL/min/1.73 m2 vs. 69 (58.1-80.4) MDRD, mL/min/1.73 m2, a p-value of 0.001 This difference is because patients who undergo nephrostomy have a lower baseline eGFR before the procedure, and renal function tests are carried out over more extended periods [4].…”
Section: Discussionsupporting
confidence: 55%